2021
DOI: 10.1007/s11063-020-10380-y
|View full text |Cite
|
Sign up to set email alerts
|

On Regularization Based Twin Support Vector Regression with Huber Loss

Abstract: Twin support vector regression (TSVR) is generally employed with ε-insensitive loss function which is not well capable to handle the noises and outliers. According to the definition, Huber loss function performs as quadratic for small errors and linear for others and shows better performance in comparison to Gaussian loss hence it restrains easily for a different type of noises and outliers. Recently, TSVR with Huber loss (HN-TSVR) has been suggested to handle the noise and outliers. Like TSVR, it is also havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…The study continued to compare the performance of commonly used support vector regression machine (SVRM) [25], general regression neural network (GRNN) [26], and abstract data restoration network (PDRN) [27]with VS-DBN models based on neural architecture search. The experiment tests the accuracy of identifying theft data for these three models, with evaluation indicators including accuracy, recall, and F1 value.…”
Section: Application Analysis Of Vs-dbnate Diagnostic Model Based On Nasmentioning
confidence: 99%
“…The study continued to compare the performance of commonly used support vector regression machine (SVRM) [25], general regression neural network (GRNN) [26], and abstract data restoration network (PDRN) [27]with VS-DBN models based on neural architecture search. The experiment tests the accuracy of identifying theft data for these three models, with evaluation indicators including accuracy, recall, and F1 value.…”
Section: Application Analysis Of Vs-dbnate Diagnostic Model Based On Nasmentioning
confidence: 99%
“…Digitization is the foundation of IoT, including the procurement of medical laboratory equipment, reagents and consumables, technical outsourcing service customization, to intermediate links such as consultation, appointment, diagnosis, treatment, medication and rehabilitation, to the delivery of final products, services, and medical insurance [14]. At present, the degree of digitalization of the supply-side and demand-side enterprise management of medical elements is relatively low, which is a key transformation link of the medical industry chain [15][16]. The industrial Internet of Things platform will be an important driver of digitalization, and gradually realize the digitalization of procurement, digitalization of production, digitalization of management, digitalization of marketing, and transactions.…”
Section: Digitalization Of Medical Industrymentioning
confidence: 99%
“…Various studies in this regard can be found in a large number of literatures, and many scholars have proposed different SVR models based on different loss functions. Table 1 shows the advantages and disadvantages of some existing literature for SVR associated with different loss functions, that is, the loss function for ramp (Tang et al, 2018), non-convex least square loss function (Wang & Zhong, 2014), ramp least square loss function (Liu et al, 2016), Huber loss function (Chen et al, 2017;Gupta & Gupta, 2021) in its generalized form with three parameters: insensitive parameter ϵ ϵ ≥ 0 ð Þ, elastic interval parameter t t ≥ ϵ ð Þ, and the adaptive robustness parameter s 0 ≤ s ≤ 1 ð Þused to achieve the robustness of SVR. Because the nonconvex loss function rises slowly, the results obtained are more robust than the convex loss function.…”
Section: Introductionmentioning
confidence: 99%